1997
DOI: 10.1017/s0022215100136515
|View full text |Cite
|
Sign up to set email alerts
|

Primary branchial cleft carcinoma – a case report

Abstract: Primary branchial cleft carcinoma is a diagnostic challenge. The majority of cases have been shown, following the application of rigid criteria, to have developed from an occult metastasis elsewhere.We describe what we believe to be only the second reported case in a patient who fulfils all of the established criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…They have been documented as to present as parapharyngeal mass located in the supratonsillar fossa and extending to the lateral nasopharynx [12]. Exceedingly rarely, a branchial cleft anomaly may be found to be malignant on presentation [13]. A complete branchial fistula with external and internal opening is rare.…”
Section: Individual Branchial Anomaliesmentioning
confidence: 99%
“…They have been documented as to present as parapharyngeal mass located in the supratonsillar fossa and extending to the lateral nasopharynx [12]. Exceedingly rarely, a branchial cleft anomaly may be found to be malignant on presentation [13]. A complete branchial fistula with external and internal opening is rare.…”
Section: Individual Branchial Anomaliesmentioning
confidence: 99%
“…One report indicated that anomalies of the second branchial arch are slightly more common in females than in males, and that they tend to occur more often on the right side [5]. The literature contains very few descriptions of primary carcinoma of the branchial cleft [6].…”
Section: Introductionmentioning
confidence: 99%
“…8 A cervical metastasis from an occult primary may present itself at a later date, adding to the controversy. 8 The jugular lymphatics and the majority of branchial cysts are also found in similar regions. Additionally, it is histologically difficult to distinguish a branchial cleft carcinoma from a metastatic cervical lymph node.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, it is histologically difficult to distinguish a branchial cleft carcinoma from a metastatic cervical lymph node. 8 For this reason, the stringent criteria of Martin et al were established. 2 In the case presented, we have evidence of a benignappearing left branchial cleft cyst by MRI imaging more than 2 years prior to the diagnosis of squamous cell carcinoma arising in the same cyst ( Figs.…”
Section: Discussionmentioning
confidence: 99%